Digital flow - from planning to execution of aesthetic oral rehabilitation: systematic review (Research, Society and Development, 2023)
Objective: To present the digital tools aimed at the planning and execution of aesthetic oral rehabilitations compared to the traditional workflow, through a systematic review of the literature. Methodology: Based on the PRISMA guidelines, registered in the PROSPERO database (CRD42022357348), a systematic search was carried out in the PubMed, BVS and Cochrane Library databases, for clinical studies in English, Portuguese and Spanish, which allowed the assessment of the use of digital workflow in aesthetic oral rehabilitation. The selection of studies for the assessment of methodological quality and data collection was carried out independently by three reviewers and a fourth mediator. Results: Eight studies have been included. The following criteria were evaluated: proximal contacts, dynamic occlusion, aesthetics, and function. In addition to the type of preparation, specific aspects of the dental element such as surfaces and angulations.  Final considerations: In view of what has been exposed, the aid of digital tools has become a means for the success of oral rehabilitation. Thus, with the technological advances in dentistry, there is a need for constant updating of dentists.